2015
DOI: 10.1002/ceat.201400790
|View full text |Cite
|
Sign up to set email alerts
|

Modified Photobioreactor for Biofixation of Carbon Dioxide by Chlorella vulgaris at Different Light Intensities

Abstract: The performance of a modified bioreactor inside a light enclosure for carbon dioxide biofixation by Chlorella vulgaris was investigated. The influence of different light intensities on the CO 2 biofixation and biomass production rates was evaluated. The results showed that the photon flux available to the microalgal cultures can be a key issue in optimizing the microalgae photobioreactor performance, particularly at high cell concentrations. Although the optimal pH values for C. vulgaris are in the range of 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
(33 reference statements)
2
3
0
Order By: Relevance
“…Reducing the light intensity to below (250 µE m -2 s -1 ) enhances the algal growth, corroborating outputs from a previous study [30].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Reducing the light intensity to below (250 µE m -2 s -1 ) enhances the algal growth, corroborating outputs from a previous study [30].…”
Section: Discussionsupporting
confidence: 89%
“…6). Previous studies based on the same algal strain using an unfiltered light (U P ) source at light intensities of 100 and 50 μE m -2 s -1 compared with 250 μE m -2 s -1 in the current study and [30] suggests unfiltered light to be 33-50% less effective at promoting algal growth and 75% less effective at promoting lipid productivity than filtered CT W in the current study. U P indicated a similar trend of about 20-30% reduced influence in supporting algal growth compared with CT W , although there was a slight enhancement in U P of about 13-20% in algal growth compare with U as a results of lower light intensity used in U P .…”
Section: 4supporting
confidence: 45%
See 1 more Smart Citation
“…Approximately 70% of microalgae and cyanobacteria carbon capture trials have used open pond growth systems, which require substantial land and water, are vulnerable to biological contamination [18], and are exposed to variable weather and climate conditions, which compromise performance. Closed culture systems (photobioreactors, PBR) can overcome many of these drawbacks [19][20][21]; however, PBRs are not without their operational, performance, and sustainability challenges [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Under the double action, the density of the algae liquid drops sharply. Naderi, Tade, and Znad (2015) studied the effects of aeration conditions on the growth of Chlorella in different reactors. They found that the more uniform distribution of algal cells and nutrients is a prominent advantage in increasing ventilation, but higher aeration results in greater friction and shear forces, which is detrimental to the growth of microalga.…”
mentioning
confidence: 99%